2010
DOI: 10.1590/s0103-90162010000400003
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin in maturation media fails to improve oocyte maturation, embryo development rates and DNA damage of bovine embryos

Abstract: Melatonin (MEL) acts as a powerful scavenger of free radicals and direct gonadal responses to melatonin have been reported in the literature. Few studies, however, have evaluated the effect of MEL during in vitro maturation (IVM) on bovine embryos. This study tested the addition of MEL to maturation medium (MM) with no gonadotropins on nuclear maturation and embryo development rates and the incidence of DNA damage in resulting embryos. Cumulus-oocyte complexes were aspirated from abattoir ovaries and cultured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 33 publications
0
4
1
1
Order By: Relevance
“…Contrary to our previous results (Soto‐Heras et al, ) we did not find a higher blastocyst yield with melatonin. Other studies neither found improvement on blastocyst production (Casao et al, ; Rodrigues‐Cunha et al, ; Takada, Martins Junior, Mingoti, Balieiro, & Coelho, ) which denotes a variability in results depending on specific culture conditions. However, we observed an increase on the ICM number and ICM:TE ratio in hatched blastocysts.…”
Section: Discussionmentioning
confidence: 92%
“…Contrary to our previous results (Soto‐Heras et al, ) we did not find a higher blastocyst yield with melatonin. Other studies neither found improvement on blastocyst production (Casao et al, ; Rodrigues‐Cunha et al, ; Takada, Martins Junior, Mingoti, Balieiro, & Coelho, ) which denotes a variability in results depending on specific culture conditions. However, we observed an increase on the ICM number and ICM:TE ratio in hatched blastocysts.…”
Section: Discussionmentioning
confidence: 92%
“…In contrast, melatonin exhibits the most desirable characteristics of a good antioxidant, scavenging a wide variety of free radicals (Galano et al, 2011). Its protective action has been described for different reproductive biotechnologies such as in vitro oocyte maturation in buffalo (Manjunatha et al, 2009) and cattle (Tsantarliotou et al, 2010;Takada et al, 2010Takada et al, , 2012Sampaio et al, 2012) improving sperm functionality in buffalo (Li et al, 2012), ram (Kaya et al, 2000;Casao et al, 2010), boar (Jang et al, 2010), mouse (Sarabia et al, 2009), hamster (Fujinoki, 2008) and human spermatozoa (Espino et al, 2010), stimulating embryo development in mice (Ishizuka et al, 2000;Gao et al, 2012), buffalo (Manjunatha et al, 2009) and cattle (Papis et al, 2007) and improving sheep embryo survival (Abecia et al, 2002). However, limited research has examined its impact on bull sperm functionality, especially during the incubation time of IVF protocol.…”
Section: Introductionmentioning
confidence: 99%
“…According to Takada et al (2010) supplementation with a physiological concentration of melatonin (10 -9 M) in in vitro maturation medium with or without a combination of gonadotropins has no effect on nuclear maturation or on rates of cleavage and blastocyst formation. These rates ranged from 88% to 90%, 85% to 88%, and 42% to 46%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant action of melatonin is a good alternative to the in vitro production of bovine embryos. When used during the embryo maturation and cultivation processes, there are decreases in ROS and DNA fragmentation in oocytes and blastocysts (Asgari et al, 2012;Takada et al, 2010;Takada et al, 2012). However, few results have been described in the literature, especially regarding melatonin concentration to be used.…”
Section: Introductionmentioning
confidence: 99%